12. Antibacterial Activity of Ethanol Extract of Siamih Leaf (Ageratum conyzoides) on Staphylococcus aureus bacteria - divina dinda hayati; Herrialfian Herrialfian; M. Isa; Darmawi Darmawi; Fakhrurrazi Fakhrurrazi; Abdul Harris (Jurnal Medika Veterinaria, 2020)
The aim of this research is to know the effect of siamih leaf ethanol extract (Ageratum conyzoides) on the growth of Staphylococcus aureus bacteria. The bacteria which is  used are obtained from the Microbiology Laboratory of the Faculty of Veterinary Medicine of Syiah Kuala University on isolate bacteria of the honey bear wound (Helarctos malayanus). Bacterial identification is done by culturing the isolate on lateral NA media then it is planted on MSA media and  staining Gram, catalase test and hemolysis test. The extraction is done by maceration with 96% ethanol solvent. Extract of Siamih leaf  is done by phytochemical test. The results of pythritic test of Siamih leaf show that Siamih leaf contains alkaloid compounds, steroids, terpenoids, flavonoids and tannins. The extract concentration which is used is 20%, 40%, 60% and 80%. Nergative control by using aquades and positive controls using Amoxicillin with three repetitions. The method used is disc diffusion or Kirby-Bauer method. The results show that Siamih leaf ethanol extract inhibit the growth of Staphylococcus aureus bacteria at concentrations of 20% (0,7 mm), 40% (1,4 mm), 60% (2,2 mm), and 80 % (3,0 mm). Thus it can be concluded that the extract of siamih leaf ethanol has inhibitory power to Staphylococcus aureus bacteria with low category.